The past and future of delusions research: from the inexplicable to the treatable. - Garety, P; Freeman, D (2013)
BACKGROUND: Problems with the diagnosis and treatment of schizophrenia have led for a call to change strategy and focus on individual psychotic experiences. In recent years, research on delusions has led the way. AIMS: To update our 1999 review of almost 40 studies on delusions. METHOD: A systematic literature search was conducted of reasoning and affective processes related to delusions. RESULTS: Over 200 studies were identified. The presence of 'jumping to conclusions' in individuals with delusions has been substantiated, the theory of mind account has not stood up to subsequent testing, and there is a promising new focus on the ways that affective processes contribute to delusional experience. CONCLUSIONS: Theoretical work rendering delusions understandable can be translated into treatment; future clinical trials should focus on individual psychotic experiences as outcomes.